Financial Stress, Time Management, and Work Intensity: Predicting Academic Performance Among Part-Time Working Students - Aulia Sugma Majiida; Nimas Aulia Pambajeng Miftahunnajah (Journal of Educational Management Research, 2026)
The increasing number of university students engaged in part-time employment has created challenges in balancing academic responsibilities with financial and occupational demands. This study aimed to examine the effects of financial stress, time management, and part-time work intensity on students' academic performance. A quantitative approach with a causal research design was employed. Data were collected through an online questionnaire using a five-point Likert scale from 100 part-time working undergraduate students selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings revealed that financial stress has a significant negative effect on academic performance, whereas time management and part-time work intensity have significant positive effects, with time management emerging as the strongest predictor. Collectively, the three independent variables explained 37.8% of the variance in academic performance, indicating that both financial and behavioral factors play important roles in shaping students' academic achievement. These findings contribute to the integration of financial, behavioral, and occupational perspectives in explaining academic performance among part-time working students. Practically, the study highlights the importance of developing institutional strategies that strengthen students' financial resilience, time management skills, and self-management competencies to support sustainable academic success while preparing them for future professional responsibilities.